Australia and the Great War : identity, memory and mythology - Walsh, Michael J. K., 1968-; Varnava, Andrekos (MUP academic history series, 2016)
Australia and the Great War explores both the immediate and long-term consequences of the war on this complex relationship, looking in particular at identity, history, gender, propaganda, economics and nationalism. This multidisciplinary collection of essays unveils the creation and subsequent [mis]use of histories and mythologies while considering the necessity and nature of both remembering, and forgetting, war.